2022
DOI: 10.1097/wnp.0000000000000932
|View full text |Cite
|
Sign up to set email alerts
|

Creating a New Set of Milestones for the Clinical Neurophysiology Fellowship

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The updated goals should serve as a guide for program directors when assessing the competency of the Epilepsy and CNP fellows. Similarly, there is a need to update the current CNP guidelines 10 and specify the competencies a fellow must achieve in regards to the surgical management of patients with epilepsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The updated goals should serve as a guide for program directors when assessing the competency of the Epilepsy and CNP fellows. Similarly, there is a need to update the current CNP guidelines 10 and specify the competencies a fellow must achieve in regards to the surgical management of patients with epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…9 Similarly, the ACGME clinical neurophysiology (CNP) milestones indicate that a CNP fellow must demonstrate detailed knowledge of advanced treatment options for medically refractory epilepsy. 10 Prior studies have shown deficiencies and lack of consistency in the education of neurology residents to achieve the required milestones for EEG interpretation. 11,12 Notably, there is scarce literature assessing the quality of surgical education in epilepsy and CNP trainees.…”
mentioning
confidence: 99%
“…One of the challenges of assessing competency in EDx is the diversity of experiences and requirements of learners, including physical medicine and rehabilitation (PM&R) residents, adult and child neurology residents, neuromuscular medicine fellows, and clinical neurophysiology fellows. Standards for training are set by the Accreditation Council of Graduate Medical Education (ACGME) and the medical board organizations that certify candidates in each of these fields, but the program requirements and milestones needed for different competency domains vary across disciplines 1–4 . For instance, the ACGME adult neurology program requirements do not even mention EDx and have no procedural minimums 1 .…”
mentioning
confidence: 99%
“…The ACMGE program requirements for PM&R, however, mandate participation in a minimum of 200 EDx evaluations, and the PM&R milestones include performing, documenting, and interpreting EDx studies 2 . Clinical neurophysiology and neuromuscular medicine fellowships require familiarity with uncommon studies that assess cranial nerve function, neuromuscular junction function, and late responses 3,4 …”
mentioning
confidence: 99%
See 1 more Smart Citation